174k views
1 vote
If g(x)=5x-3 and h(x)= sqaure root of x find (g o h)(4)

2 Answers

3 votes

Answer:
(g o h)(4)=7

Explanation:

Given the function g(x):


g(x)=5x-3

And the function h(x):


h(x)=√(x)

We need to plug the function
h(x)=√(x) into the function
g(x)=5x-3, in order to find
(g o h)(x) . Then:


(g o h)(x)=5(√(x))-3


(g o h)(x)=5√(x)-3

Now, in order to find
(g o h)(4), we need to substitute
x=4 into
(g o h)(x)=5√(x)-3. Then, this is:


(g o h)(4)=5√(4)-3


(g o h)(4)=10-3


(g o h)(4)=7

User Franz Gastring
by
5.0k points
3 votes

Answer:

The answer is 7

Explanation:

We have:

if g(x)=5x-3 and h(x)= sqaure root of x.

We have to find (g o h)(4).

(g o h) = g(h(x))

Plug the value of h(x) which is √x in g(x)

g(h(x))= g(√x)

Now plug the value √x in g(x).

g(h(x))= g(√x) = 5√x-3

Now to find (g o h)(4) plug in 4 in place of x

(g o h)(x)=g(h(x))= g(√x) = 5√x-3

(g o h)(4)= g(h(4)) = g(√4) = 5√4-3

Therefore:

(g o h)(4) = 5(2)-3

(g o h)(4) = 10-3 = 7

Thus the answer is 7....

User Vadimich
by
5.0k points